1980
DOI: 10.3758/bf03329570
|View full text |Cite
|
Sign up to set email alerts
|

Effects of early protein malnutrition on learning in the rat

Abstract: Animals were reared on a diet of commercially available corn grits from weaning to approximately 120 days of age. Littermate controls were fed Purina Laboratory Chow. The subjects' learning ability was tested in a two-way active avoidance task and a black-white visual discrimination task. The grits-fed animals did not develop physically and remained as small as weanling rats throughout the study. The data from the learning tasks indicate that there were no differences in learning ability between the protein-ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
5
1

Year Published

1989
1989
1993
1993

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 10 publications
3
5
1
Order By: Relevance
“…First, the weight differential that developed between the two groups during the grits-exposure phase corroborate the Remley et al (1980) and Becker et al (1989) reports. Clearly, the protein-and tryptophan-deficient grits diet suppressed growth and weight gain significantly.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…First, the weight differential that developed between the two groups during the grits-exposure phase corroborate the Remley et al (1980) and Becker et al (1989) reports. Clearly, the protein-and tryptophan-deficient grits diet suppressed growth and weight gain significantly.…”
Section: Discussionsupporting
confidence: 77%
“…fect in grits-exposed rats by 75 days of age, and (2) even more dramatic effects were produced by placing nursing dams on the experimental diet coincident with the birth of the pups, Becker, Davis, Grover, and Erickson (1989) extended the Remley et al (1980) data. Without question, the protein-and tryptophan-deficient grits diet produces animals that, at maturity, differ significantly from normally reared littermates.…”
mentioning
confidence: 88%
“…Unfortunately, these were the only weighings reported by Remley et al (1980). Hence, a complete picture of the growth curve of animals raised under these conditions has yet to be developed.…”
mentioning
confidence: 99%
“…For example, Zimmerman, Geist, and Strobel (1975) failed to report differences in delayed-response, leaming-set, objectdiscrimination, and simple reversal-leaming tasks in monkeys. Likewise, Remley, Armstrong, Gilman, and Mercer (1980) reported that rats raised on a protein-deficient diet from weaning to maturity did not differ from normal littermates in terms of two-way active avoidance and blackwhite visual discrimination performance. Hence, the question of diminished cognitive capacities awaits further experimental verification.…”
mentioning
confidence: 99%
See 1 more Smart Citation